Legal regulation of the genesis of digital identity - O. A. Stepanov; M. M. Stepanov (Правоприменение, 2022)
The article deals with a new phenomenon for the legal science – the institute of legal regulation of the genesis of digital identity.The subject of the research is the relations that emerge in the process of such regulation. The aim of the research is to analyze the legal regulation of the institute of digital identity at the international, regional and national levels, including in the Russian Federation.The methodological basis of the research is the logical and systematic methods of scientific knowledge, as well as methods of analysis and synthesis, formal-dogmatic and comparative-legal methods.International, foreign and domestic experience in the genesis of digital identity is studied. The features of legal regulation of each of the elements of digital identity – digital profile, digital image, digital footprint – are analyzed. At the same time, the legal regulation of the relevant relations is considered in their dynamics. As a result of the study, conclusions were made about the peculiarities of international legal regulation of relations related to the genesis of a legal identity, the legal regulation of these relations in the European Union and China. It is noted that international legal regulation of relations related to the genesis of legal personality is carried out, as a rule, only in connection with the need to protect human rights and freedoms in the digital age, including in virtual space; in the European Union the legal regulation is mainly subject to the digital profile of the person, based on his personal data; at the level of individual states the most holistic and systemic regulation of relations related to digital identity is carried out in the People's Republic of China on the Special attention is given to the problems of legal regulation of the genesis of digital identity in the Russian Federation. It is noted that the problems of legal regulation of the genesis of digital identity are becoming particularly relevant at the present time. Its theoretical comprehension is a prerequisite for improving current legislation and law enforcement practice in the Russian Federation.It is pointed out that there are significant gaps in the legal regulation of relations related to the digital footprint in Russia, the most regulated relations in the area of digital profile and digital image; further lack of legal regulation of the collection and processing of information that constitutes the content of the digital identity footprint in Russia will lead to a massive violation of individual rights and freedoms.The study also found that the international legal regulation of relations related to the genesis of the legal personality is usually carried out only in connection with the need to protect human rights and freedoms in the digital age, including in virtual space, and in the European Union the legal regulation is mainly subject to the digital profile of the person, which is based on his personal data.